Complex interaction of subsequent surface streamers via deposited charge: a high-resolution experimental study. (17th May 2017) - Hoder, T; Synek, P; Chorvát, D; Ráhel', J; Brandenburg, R; Černák, M
Abstract: The coplanar barrier discharge in synthetic air at 30 kPa pressure was studied by time-correlated single photon counting enhanced optical emission spectroscopy, far-field microscopy enhanced intensified CCD camera and sensitive current measurements. The discharge operated in a regime where two subsequent microdischarges appeared within the same voltage half-period. The electrical analysis of the barrier discharge setup enabled us to quantify charge transfer and the effective electric field development. During the second microdischarge the positive surface streamers follow the interface (triple-line) between the area of deposited charge from the previous one and the area of uncharged dielectric surface. It is shown that additional branching and flashes of surface streamers are responsible for the increased spatial complexity of the deposited surface charges at high overvoltage. A suppressed streamer propagating over the area of deposited surface charge was tracked and the evidence of surface streamer reconnection is presented. A spatiotemporal distribution (resolution of 120 ps and 100 μ m) of the reduced electric field strength was obtained for both microdischarges from the recorded luminosities of the molecular nitrogen. The reduced electric field of positive streamers in the first microdischarge reached 1200 Td. For the second one, the electric field values for the streamer at the triple-line are slightly lower than that, while for the suppressed streamers are even higher.